Challenges and Reforms in the Implementation of Collateral Seizure on Land within Indonesia’s Banking System: A Study of the Mortgage Law - Nurwidianto, Eko; Setyowati, Retno Kus; Mutiarany, Mutiarany (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2024)
This study aims to analyze the challenges faced in the implementation of collateral seizure on land mortgages in Indonesia, particularly in the context of legal uncertainty and complicated execution procedures. Using a descriptive method and a juridical-normative approach, this study finds that the main issue in the execution of land collateral is the uncertainty regarding the ownership status of the land, often caused by unresolved land disputes or unregistered ownership. Additionally, the land execution process, which involves lengthy court procedures and the existence of land mafia, further worsens the efficiency of execution. Based on these findings, the study suggests several reforms, including improvements to the land registration system, more efficient judicial procedures, and enhanced legal protection for all parties involved. These reforms are expected to accelerate and simplify the process of executing land collateral as a legitimate and accountable form of credit guarantee.